Association between incident falls and subsequent fractures in patients attending the fracture liaison service after an index fracture: a 3-year prospective observational cohort study - Piet Geusens; Jacqueline R Center; Tuan V Nguyen; Thach Tran; Johanna Driessen; Joop P van den Bergh; John Eisman; Caroline E Wyers; Lisanne Vranken; Robert Y Van der Velde; Heinrich M J Janzing; Sjoerd Kaarsemakers; et al. (BMJ Open)
Objectives To evaluate the risk of subsequent fractures in patients who attended the Fracture Liaison Service (FLS), with and without incident falls after the index fracture.Design A 3-year prospective observational cohort study.Setting An outpatient FLS in the Netherlands.Participants Patients aged 50+ years with a recent clinical fracture.Outcome measures Incident falls and subsequent fractures.Results The study included 488 patients (71.9% women, mean age: 64.6±8.6 years). During the 3-year follow-up, 959 falls had been ascertained in 296 patients (60.7%) (ie, fallers), and 60 subsequent fractures were ascertained in 53 patients (10.9%). Of the fractures, 47 (78.3%) were fall related, of which 25 (53.2%) were sustained at the first fall incident at a median of 34 weeks. An incident fall was associated with an approximately 9-fold (HR: 8.6, 95% CI 3.1 to 23.8) increase in the risk of subsequent fractures.Conclusion These data suggest that subsequent fractures among patients on treatment prescribed in an FLS setting are common, and that an incident fall is a strong predictor of subsequent fracture risk. Immediate attention for fall risk could be beneficial in an FLS model of care.Trial registration number NL45707.072.13.